Análisis Financiero a la Cooperativa de Ahorro y Crédito Campesina “COOPAC” Ltda. en la ciudad de Ambato, período 2020 – 2021. - Soto Quevedo, Juan Carlos (2023)
The curricular integration work "Financial Analysis of the Savings and Credit Cooperative "COOPAC" Ltda, in the city of Ambato, Period 2020-2021, was developed in order to meet the objectives set, so to comply with them, we proceeded to collect the necessary documentation in order to develop the vertical analysis of the financial statements, which establishes the financial structure and participation of the equivalent percentages of each account involved in the economic and financial position of the cooperative, In addition, the horizontal analysis was carried out in which the financial movements and variations are established, being these increases or decreases of the figures in the financial statements included in the period of study 2020-2021. In the same way, the financial indicators established by the Superintendence of Popular and Solidarity Economy (SEPS) were applied, which allowed establishing the equity solvency that can efficiently solve the non-productive assets, with respect to the delinquency rates, the recovery of past due portfolio was reflected, the Coverage of the Non-productive Portfolio to the year 2021 was relevant due to the provisions made, the Liquidity for the last period; The liquidity for the last period, a significant value that allows it to respond to short-term obligations, and the Vulnerability of the Equity with an adequate percentage that is sufficient to respond to possible credit risks. Finally, the financial report has been developed in a concrete manner where the results of the analysis were presented, as well as conclusions and recommendations that contribute to the managers and administrators to make decisions focused on the improvement of the activities of the Savings and Loan Cooperative.